Isoelectric Focusing of Cerebrospinal Fluid Significance in Differential Diagnosis of Multiple Sclerosis - Grgić, Sanja; Dominović Kovačević, Aleksandra; Vukojević, Zoran; Tadić, Daliborka; Nazalević Bursać, Majda (Scripta Medica, 2025)
Background/Aim: Isoelectric focusing (IEF) of cerebrospinal fluid (CSF) is the gold standard for detecting intrathecal oligoclonal immunoglobulin G (IgG). Besides its diagnostic and predictive significance, the IEF method also has differential diagnostic impact in multiple sclerosis (MS). The goal of the research was to analyse the influence of IEF on the differential diagnosis of MS, as well as in neurology in general. Methods: Research included 418 participants treated in the Neurology Clinic of the University Clinical Centre of the Republic of Srpska. Among them, 177 were suffering of MS. The control group, divided into major disease categories, consisted of 241 patients. The following were analysed for participants: demographic and clinical characteristics, IEF and cytobiochemical findings of CSF. Based on IEF findings, participants with oligoclonal bands (OB) were separated from those without OB. The findings of IEF in different disease categories and their differential diagnostic significance were analysed. Results: In the examined cohort using the IEF method, intrathecal synthesis of oligoclonal IgG was evident only in inflammatory diseases, primarily multiple sclerosis and was absent in any non-inflammatory diseases. This indicated high sensitivity of the method for MS patients (96.6 %) and very high specificity for CNS inflammatory diseases (100 %). Conclusion: IEF is a highly specific for CNS inflammatory diseases, indicating the differential diagnostic significance of oligoclonal IgG in MS, as well as in neurology in general.